Aberrant expression of KOR-SA3544 antigen in childhood acute lymphoblastic leukemia predicts TEL-AML1 negativity. The Pediatric Hematology Working Group in the Czech Republic - Hrusák, O; Trka, J; Zuna, J; Housková, J; Bartůnková, J; Starý, J (Leukemia, 1998)
The antigen KOR-SA3544 is physiologically expressed exclusively on granulocytes. Aberrant expression of KOR-SA3544 has been invariably found in BCR/ABL-positive acute lymphoblastic leukemia (ALL) and in some BCR/ABL-negative ALL. In an interim analysis of a prospective clinical and cytometric study data of 73 children with newly diagnosed or relapsed ALL with and without TEL/AML1 fusion are presented. KOR-SA3544 expression over 3% was detected in the majority of TEL/AML1-negative patients with newly diagnosed common or preB ALL (19 of 31) and not in TEL/AML1-positive patients (0 of 18, P < 0.0001). The level of expression of KOR-SA3544 was 0.02-90% (median 6.0%) and 0.03-2.4% (median 0.23%) in TEL/AML1-negative and TEL/AML1-positive patients, respectively. All five newly diagnosed patients with DNA index > or =1.16 and <1.6 exhibited high levels of KOR-SA3544 expression. Membrane expression of CD79a was found to correlate with TEL/AML1 negativity, although less significantly than KOR-SA3544 (P = 0.03). Furthermore, our data confirm that TEL/AML1 positivity correlates with non-hyperdiploidy and low presenting age. In conclusion, KOR-SA3544 correlated strongly with TEL/AML1 negativity, it was a better predictor of TEL/AML1 status than other factors tested and was found at high levels in hyperdiploidy. In combination with age, KOR-SA3544 predicted TEL/AML1 status in 86% newly diagnosed preB/cALL patients.
Keywords: umělá fúze genů; protoonkogenní proteiny c-ets; represorové proteiny; polymerázová řetězová reakce; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; pre-B-buněčná leukemie; protein ETS, translokační varianta 6; protein PEBP2A2; Child; Proto-Oncogene Proteins; antigeny nádorové; DNA nádorová; dítě; ETS Translocation Variant 6 Protein; Age Factors; ploidie; DNA vazebné proteiny; akutní lymfatická leukemie; DNA, Neoplasm; Precipitin Tests; Core Binding Factor Alpha 2 Subunit; lidé; Transcription Factors; transkripční faktory; Humans; precipitinové testy; věkové faktory; Antigens, Neoplasm; Repressor Proteins; Artificial Gene Fusion; Proto-Oncogene Proteins c-ets; Polymerase Chain Reaction; Ploidies; Precursor Cell Lymphoblastic Leukemia-Lymphoma; DNA-Binding Proteins; protoonkogenní proteiny